Quantitative Imaging Approaches to Study the CAR Immunological Synapse - Mukherjee, Malini (Mol Ther, 2017)
The lytic immunological synapse (IS) is a discrete structural entity formed after the ligation of specific activating receptors that leads to the destruction of a cancerous cell. The formation of an effector cell IS in cytotoxic T lymphocytes or natural killer cells is a hierarchical and stepwise rearrangement of structural and signaling components and targeted release of the contents of lytic granules. While recent advances in the generation and testing of cytotoxic lymphocytes expressing chimeric antigen receptors (CARs) has demonstrated their efficacy in the targeted lysis of tumor targets, the contribution and dynamics of IS components have not yet been extensively investigated in the context of engineered CAR cells. Understanding the biology of the CAR IS will be a powerful approach to efficiently guide the engineering of new CARs and help identify mechanistic problems in existing CARs. Here, we review the formation of the lytic IS and describe quantitative imaging-based measurements using multiple microscopy techniques at a single cell level that can be used in conjunction with established population-based assays to provide insight into the important cytotoxic function of CAR cells. The inclusion of this approach in the pipeline of CAR product design could be a novel and valuable innovation for the field.